Effects of the Calisthenic Exercise Program in the Physical Education Teaching on the Elementary School Pupils' Motor Abilities - Aleksandar J. Gadžić (University of Belgrade, Teacher Education Faculty, 2020)
The development of humanity is directed towards general progress, but one of the negative consequences of that progress is that children are increasingly living a sedentary lifestyle, that they are increasingly becoming obese, and that they adopt bad behavioral patterns. One of the ways to encourage students to engage in a regular physical activity is to present it to them in an interesting way, with adequate methods, tools and content. The goal of this research is to determine the effects of the program of calisthenic exercises on the motor abilities of elementary school children. The research is an experimental study with parallel groups of 50 students from two fifth-grade classes. After an experimental program that lasted 10 weeks during regular physical education classes, it was determined that the boys in the experimental group achieved better results than the boys in the control group on three of the eight motor tests, while no statistically significant differences were found in girls. However, in the girls of the experimental group, progress in motor abilities was determined between the initial and final measurement, while in the girls of the control group this was not the case. The applied program of calisthenic exercises can lead to positive transformations of motor abilities, and the recommendation for future research is to enrich the content with the use of various props and music, which would probably lead to a greater engagement of girls and boys during exercise.